Uso do óleo residual de fritura na dieta de cordeiros - Oliveira, Jéssica Taiomara Moura Costa Bezerra de (2018)
The objective of this study was to evaluate the performance of sheep, carcass characteristics, non-carcass components, meat quality of animals submitted to diets with different levels of residual frying oil (0, 3, 6 and 9%). Twenty-four animals with no defined racial pattern, male and uncastrated, were randomly assigned to four treatments and six replicates. The animals were confined for a period of 46 days, after 14 days of adaptation, weighed at the beginning and end of the experimental period to evaluate daily and total weight gain, and slaughtered at 180 days of age. The diet used was composed of bulky and concentrated in the ratio 40:60, ad libitum, supplied daily at 8:00 am and 4:00 p.m., calculating a surplus of 10%. The nutritional levels of the diet were balanced according to the recommendations of NRC (2007), for gain of 200g daily. Daily samples of the supplied and leftover samples were collected and analyzed for dry matter, mineral matter, crude protein, neutral detergent fiber, acid detergent fiber, lignin and ethereal extract, and total carbohydrate contents were calculated. non-fibrous carbohydrates, voluntary consumption of nutrients, calculated by the quantity supplied and the quantity refused by the animals. After slaughter, the weight of the warm carcass was recorded, the weight of the empty body obtained by the difference between the live weight at slaughter and the gastrointestinal content. The pH and temperature were checked through a portable digital pH meter, then the carcasses were taken to the cold chamber with plastic protection, where they remained for 24 hours. At the end of this period the cold carcass weight was verified and the carcass yields, cold carcass yields and true yield were calculated. Losses were also determined on cooling and removal of Longíssimus dorsi muscle from the loin and rib, which were identified, packed in a polyethylene bag and sent for analysis. Meat samples were analyzed for the following microorganisms: Mesophiles, Psychrotrophs and Salmonella ssp., As well as physical analyzes (pH, color, water retention capacity, weight loss per cooking, shear force) and chemical (moisture , ashes, protein and lipids). During the experiment there was a difference (P <0.05) in the dry matter intake, as well as the total weight gain was also significantly influenced (P <0.05), being the 9% oil inclusion treatment performance. The performance, the warm and cold carcass weight were also influenced (P <0.05) by the treatment, obtaining a lower average treatment of 9% inclusion of residual frying oil. The weights of the non-carcass components did not present statistical difference (P> 0.05), except for the paws, this parameter possibly was influenced by the lack of a defined racial pattern. The meat quality characteristics also showed no difference (P> 0.05), which indicates that the inclusion of the residual frying oil could be allowed up to 9% without changing the quality of the meat. Therefore, taking into account the performance of lambs, up to 6% of residual frying oil may be included in the diet